25 years of Regulation of Water Services; looking backwards & forwards1, 2. (October 2017) - Byatt, Ian
Abstract: Sir Ian Byatt was the first regulator of the water and wastewater industry in England and Wales (Director General of Water Service) from privatisation in 1989–2000. He examines the experience of a quarter of a century of the regulation of water companies, concentrating on what worked well and where further developments are needed to deal with changing circumstances. He concludes that while RPI-X regulation, combined with comparative competition, worked well with respect to operating expenditure, the regulation of capital expenditure needs enhancement to avoid overcharging of customers. He advocates the development of performance regulation, backed by project competition, where customers pay for quality enhancement only when they receive it. Highlights: The first regulator of the water and wastewater industry in England and Wales assess results. He looks at 25 years experience of privatisation, commending RPI-X regulation. The regulation of capital expenditure needs better relation to performance. Customers should pay for enhanced service only when they receive it.